2018
DOI: 10.1108/maj-11-2017-1692
|View full text |Cite
|
Sign up to set email alerts
|

Consumer security behaviors and trust following a data breach

Abstract: Purpose The purpose of this study was to determine how security statement certainty (overconfident, underconfident and realistic) and behavioral intentions of potential consumers impact the perceptions of companies in the presence or absence of a past security breach. Design/methodology/approach The study exposed participants to three types of security statements and randomly assigned them to the presence or absence of a previous breach. Participants then evaluated the company and generated a hypothetical pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Specifically, Belanger et al (in Curtis et al, 2018) found that the attractive features of online use more generally determined trust in companies, then by the perceived security features. Curtis et al (2018) also found that individuals expressed more trust in the corporate when the corporate had never experienced a security breach. The financial and startup sector sees FinTech as a passage to expand business openings, be that as it may, versatile applications and other innovation stages must be propelled to investigate such prospects.…”
Section: The Influence Of Application Security On Trustmentioning
confidence: 87%
See 2 more Smart Citations
“…Specifically, Belanger et al (in Curtis et al, 2018) found that the attractive features of online use more generally determined trust in companies, then by the perceived security features. Curtis et al (2018) also found that individuals expressed more trust in the corporate when the corporate had never experienced a security breach. The financial and startup sector sees FinTech as a passage to expand business openings, be that as it may, versatile applications and other innovation stages must be propelled to investigate such prospects.…”
Section: The Influence Of Application Security On Trustmentioning
confidence: 87%
“…Indeed, even among numerous people who have the capacity and information, however, not engaged with fundamental (yet, tedious) exercises that will protect traded off security. For example, impairing treats, perusing administration understandings to utilize individual data, and using a safe inquiry structure (Curtis et al, 2018). Numerous components impact trust in receiving FinTech advancements, for instance, information privacy, accessibility, respectability, constant wireless connections, the usability of mobile applications, transaction security, cultural influence, and organizational trust.…”
Section: The Influence Of Application Security On Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…Using reported security breaches during the period 2005-2014, results reveal that firms with technology committees are more likely to have reported breaches in a given year than are firms without the committee Carré et al, 2018 Ascribing responsibility for online security and data breaches Exploratory study. The authors reveal that individuals held companies more responsible for protecting private data and held companies even more responsible following a data breach Curtis et al, 2018 Consumer security behaviors and trust following a data breach Exploratory study. The authors' summary is that online security is of great concern and companies that have had a breach face reputational damage Smith et al, 2018 Do Auditors Price Breach Risk in Their Audit Fees?…”
Section: Methodsmentioning
confidence: 99%
“…No. of citations Amir et al, 2018;Carré et al, 2018;Curtis et al, 2018;Ettredge et al, 2018;Gordon et al, 2018;Gyun No and Vasarhelyi, 2017;Islam et al, 2018;Kahyaoglu and Caliyurt, 2018;Li et al, 2018;Rahimian et al, 2016;Smith et al, 2018;Stafford et al, 2018 12 0-4 Bose and Luo, 2014;Gansler and Lucyshyn, 2005;Gordon et al, 2016;Gordon et al, 2008;Higgs et al, 2016;Steinbart et al, 2018;Steinbart et al, 2016;Steinbart et al, 20138 5-30 Abu-Musa, 2006Gordon et al, 2015a;Gordon et al, 2015b;Hausken, 2007;Kwon et al, 2013;Pathak, 2005;Steinbart et al, 2012;Wallace et al, 2011;Wang et al, 2013 9 30-90 Boritz andNo, 2005;Ettredge and Richardson, 2003;Gordon et al, 2010;Gordon et al, 2003;Gordon and Loeb, 2002;Hausken, 2006;Lainhart, 2000;Li et al, 2012;Tanaka et al, 2005 10 90 ! Table IV.…”
Section: Authorsmentioning
confidence: 99%